Psychometric analysis of the Broome pelvic floor muscle exercise self-efficacy scale in women with urinary incontinence - Maryam Damghanian; Minoo Pakgohar; Mahmoud Tavousi; Nahid Dehghan Nayeri; Maryam Najafi; Roghieh Kharaghani; Barbara Broome; Zinat Ghanbari (Tehran University of Medical Sciences, 2018)
Background & Aim: Urinary incontinence is a common disorder in women. Pelvic floor muscle exercise is one of the effective treatment methods. Self-efficacy is considered an effective and strong predictor of willingness to perform and continue these exercises. In Iran, there is no appropriate tool for assessing self-efficacy. So this study was performed to determine the psychometric properties of the Broome scale in women with urinary incontinence. Methods & Materials: A psychometric study of the Broome scale was conducted on women with urinary incontinence who referred to health centers affiliated to Tehran University of medical sciences in 2015.In this study, following processes were implemented: translation, back translation, face validity, content validity using CVR and CVI, reliability using Cronbach's α coefficient, and construct validity using explanatory factor analysis. Results: The face validity was confirmed through the modification of ambiguous items based on the patients' views. Content validity (CVR= 0.8 and CVI= 0.8 to 0.9) and reliability (Cronbach's α= 0.96) were also confirmed. Explanatory factor analysis showed two factors with eigen value more than 1 including pelvic floor exercise self-efficacy in usual and special situations. These factors explained 82.08 percent of the total variance. Conclusion: The reliability and validity of the Broome scale were confirmed for using by Iranian women with urinary incontinence, and this scale can be used to measure these womenchr('39')s self-efficacy in performing pelvic floor exercises.